Increasing 2 -Bio- (H2 and CH4) production from food waste by combining two-stage anaerobic digestion and electrodialysis for continuous volatile fatty acids removal. (15th June 2021) - Hassan, Gamal K.; Jones, Rhys Jon; Massanet-Nicolau, Jaime; Dinsdale, Richard; Abo-Aly, M.M.; El-Gohary, Fatma A.; Guwy, Alan
Highlights: A novel combination of two stage AD and ED increased biofuels production from FW. Using ED in a hydrogen fermenter increased the hydrogen yield by factor of 1.9. ED had a positive effect on patterns of FW utilization and VFA production. Using ED and two-stage AD to treat FW increases overall bioenergy recovery by 77.1%. Abstract: A novel approach of using two stage anaerobic digestion coupled with electrodialysis technology has been investigated. This approach was used to improving bio hydrogen and methane yields from food waste while simultaneously producing a green chemical feedstock. The first digester was used for hydrogen production and the second digester was used for methane production. The first digester was combined with continuous separation of volatile fatty acids using electrodialysis. The concentrations of carbohydrates, proteins and fats in the prepared food waste were 22.7%, 5.7% and 5.2% respectively. Continuous removal of volatile fatty acids during fermentation in the hydrogen digester not only increased hydrogen yields but also increased the production rate of volatile fatty acids. As a result of continuous VFA separation, hydrogen yields increased from 17.3 mL H2 /g VS fermenter to 33.68 mL H2 /g VS fermenter. Methane yields also increased from 28.94 mL CH4 /g VS fermenter to 43.94 mL CH4 /g VS fermenter . This represents a total increase in bio-energy yields of 77.1%. COD reduced by 73% after using two stage anaerobic digestion, however, this reduction increased to 86.7% after using electrodialysis technology for separation of volatile fatty acids. Electrodialysis technology coupled with anaerobic digestion improved substrate utilization, increased bioenergy yields and looks to be promising for treating complex wastes such as food waste.